Rancang Bangun Aplikasi Complaint Management System Berbasis Web Pada Sirclo Commerce (Design And Build A Web-Based Complaint Management System Application On Sirclo Commerce) - Hermawan, Muhamad Fikri; Mulyati, Sri; Taufiq, Rohmat; Sadi, Sumardi (Universitas Muhammadiyah Tangerang, 2025)
Customer complaint handling is critical in maintaining service quality and customer satisfaction in the e-commerce industry. Currently, SIRCLO Commerce uses traditional methods that are often time-consuming and prone to errors, leading to suboptimal complaint resolution and negatively impacting customer experience. This research utilizes observation, interviews, and literature studies, along with SWOT analysis and system development using Rapid Application Development (RAD). The results indicate that complaint management at SIRCLO Commerce is not yet fully computerized, so implementing a CMS is expected to ease staff in managing customer complaints. The CMS is anticipated to enhance customer satisfaction and loyalty through quick and accurate complaint resolution, and provide insights into complaint trends for strategic decision-making. This CMS implementation could also serve as a model for other e-commerce companies, boosting their competitiveness and business sustainability in an increasingly competitive market Keywords: Complaint Management System, E-commerce, Customer Satisfaction, Customer Loyalty, Order Cancellation. AbstrakPenanganan keluhan pelanggan sangat penting dalam mempertahankan kualitas layanan dan kepuasan pelanggan di industri e-commerce. Saat ini, SIRCLO Commerce menggunakan metode tradisional yang sering memakan waktu dan rentan terhadap kesalahan, sehingga penyelesaian keluhan tidak optimal dan berdampak negatif pada pengalaman pelanggan. Penelitian ini menggunakan observasi, wawancara, dan studi pustaka, serta analisis SWOT dan pengembangan sistem dengan Rapid Application Development (RAD). Hasil penelitian menunjukkan bahwa manajemen keluhan di SIRCLO Commerce belum terkomputerisasi maksimal, sehingga implementasi CMS diharapkan mempermudah staf dalam mengelola keluhan pelanggan. CMS diharapkan meningkatkan kepuasan dan loyalitas pelanggan melalui penyelesaian keluhan yang cepat dan tepat, serta memberikan wawasan mengenai tren keluhan untuk pengambilan keputusan strategis. Implementasi CMS ini juga bisa menjadi model bagi perusahaan e-commerce lain, meningkatkan daya saing dan keberlanjutan bisnis di pasar yang semakin kompetitif. Kata Kunci: Complaint Management System, E-commerce, Kepuasan Pelanggan, Loyalitas Pelanggan, Pembatalan Order